2002
DOI: 10.1016/s0377-1237(02)80039-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Evaluation of Limb Fracture Patients

Abstract: The study included 70 consecutive patients with fracture of the lower and upper limbs each and an equal number of age and sex matched normal control subjects. AU the subjects were screened using the General Health Questionnaire (GHQ), the Michigan Alcoholism Screening Test (MAST), Carroll Rating Scale for Depression (CRSD), State-Trait Anxiety Inventory (STAI), Impact of Events Scale (IES), Fatigue Scale (FS) and the Perceived Stress Questionnaire (PSQ). Probable "Psychiatric cases" identified by the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similar findings were noted by Chaudhary et al 8 35%. Majority patients of axis I psychiatric diagnosis belongs to major depressive disorder (23%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were noted by Chaudhary et al 8 35%. Majority patients of axis I psychiatric diagnosis belongs to major depressive disorder (23%).…”
Section: Discussionsupporting
confidence: 91%
“…However, a study by Chaudhary et al 8 found that there was significant association between fracture involving limb and axis I psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…Armed Forces' a subject which has been scarcely discussed and researched with very few large scale studies to date. [2][3][4][5][6][7] The author needs to be complimented on bringing this important issue of military psychiatry to the fore by his paper on the subject. 8-10 2.…”
Section: Role Of Military Psychiatry To Tackle 'Stress In the Indianmentioning
confidence: 99%
“…A series of 140 limb fracture patients at a service hospital reported significantly higher scores on general health questionnaire, Michigan alcoholism screening test, Carroll rating scale for depression, impact of events scale, and fatigue scale. 8 The limb fracture patients also had a high prevalence of alcohol dependence/abuse and depressive disorders. The above were hospital based crosssectional studies done on in patients and cannot be generalised to soldiers in the field.…”
Section: Conceptualising Stressmentioning
confidence: 99%